2020
DOI: 10.3390/plants9050551
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic Effect of Three Ion Beams on Rice and Identification of Heritable Mutations by Whole Genome Sequencing

Abstract: High-energy ion beams are known to be an effective and unique type of physical mutagen in plants. However, no study on the mutagenic effect of argon (Ar) ion beam radiation on rice has been reported. Genome-wide studies on induced mutations are important to comprehend their characteristics for establishing knowledge-based protocols for mutation induction and breeding, which are still very limited in rice. The present study aimed to investigate the mutagenic effect of three ion beams, i.e., Ar, carbon (C) and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 39 publications
(65 reference statements)
5
20
1
Order By: Relevance
“…Dwarf rice plants caused by ion beam, as observed in the present study was previously reported by Oono et al (2020). Zheng et al (2020) showed that heavy-ion beam irradiation was effective in inducing mutations in rice, and revealed the characteristics of mutations at the genome level.…”
Section: Evaluation Of M2 Generationsupporting
confidence: 84%
“…Dwarf rice plants caused by ion beam, as observed in the present study was previously reported by Oono et al (2020). Zheng et al (2020) showed that heavy-ion beam irradiation was effective in inducing mutations in rice, and revealed the characteristics of mutations at the genome level.…”
Section: Evaluation Of M2 Generationsupporting
confidence: 84%
“…They minimize weed control costs and use less water (Oladosu et al 2014). The TGW has no significant difference (Figure 5(b)), and the results were kept decreasing from 60 to 100 Gy as reported by Zheng et al (2020), the values decreased as the dose increased. Significant differences in FR were observed between the control and all the treatments except for the two optimum doses, 40 and 60 Gy based on Tukey's HSD test (Figure 5(c)).…”
Section: Effect Of Carbon Ion Beam Irradiation On the Morpho-agronomical Traitsmentioning
confidence: 65%
“…The biological effects of ion-beams have also been investigated and observed to show a high relative biological effectiveness (RBE) in lethality, mutation and also to transfer high energy to the target compared to low LET radiation such as Gamma-rays, X-rays and electrons (Tanaka et al 2010). Since then, carbon ion beams have been used in rice breeding programs, and several useful mutant lines have been created, including low cadmium rice, UVB-tolerant mutants, and extremely late heading mutants (Zheng et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mutation profile at the genome scale can also be used for selecting a proper mutagen for mutation breeding and gene function analysis. Re-sequencing analysis of progeny of mutagenized plant material has provided a new perspective aimed at characterizing the mutation molecular profile of various physical mutagens at the whole-genome scale in the last 10 years [ 31 , 33 , 36 , 40 , 41 , 47 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. In earlier research, only one mutant line was sequenced since it was still costly to perform NGS analysis.…”
Section: Discussionmentioning
confidence: 99%